2020
DOI: 10.1002/jcla.23498
|View full text |Cite
|
Sign up to set email alerts
|

The optimized research of the in vitro culture of preantral follicles in mice

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
(104 reference statements)
1
4
0
Order By: Relevance
“…This method reduces the secondary separation of mechanical follicle stimulation and ensures the structure and function of the follicle. The results showed that follicles separated by mechanical method had a uniform diameter in size, with three to four layers of granulosa cells and intact follicular theca structure, consistent with the reported article [ 10 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This method reduces the secondary separation of mechanical follicle stimulation and ensures the structure and function of the follicle. The results showed that follicles separated by mechanical method had a uniform diameter in size, with three to four layers of granulosa cells and intact follicular theca structure, consistent with the reported article [ 10 ].…”
Section: Discussionsupporting
confidence: 91%
“…Brown et al [ 26 ] presumed that preantral follicles began to accept the regulation of hormone levels through vascular construction. In addition, we adopted the mechanical separation method in our experiment [ 10 ]. This method reduces the secondary separation of mechanical follicle stimulation and ensures the structure and function of the follicle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In female animals, FSH stimulates the growth and development of follicles, and increases the oxygen uptake of parietal granulosa cells to promote related protein synthesis [ 13 ]. Especially in the late stage of follicle formation, FSH induces granulosa cells to express a large number of luteinizing hormone receptors and their own proliferation and induces an increase in the expression of epidermal growth factor receptor (EGFR) to promote the occurrence of ovulation under the synergistic effect of LH [ 14 , 15 ]. In addition, FSH treatment up-regulated the synthesis of related hormones, including progesterone [ 16 ].…”
Section: Function and Structure Of Fshmentioning
confidence: 99%
“…This interaction between gonadotropin and oocyte paracrine factors is thought to support the physiological mechanism regulating species-specific ovulation rates and fecundity; e.g., in bovines, it is found throughout all follicle development, related to the proliferation and steroidogenesis of granulosa cells [ 135 , 136 ]. In mice, FSH was reported to induce the GCs to express LH receptors and their proliferation in the late stage of follicle formation, and to cause an increase in epidermal growth factor receptor (EGFR) to promote ovulation [ 137 , 138 ].…”
Section: Fsh In the Adult Phase: Folliculogenesis And Spermatogenesismentioning
confidence: 99%